PENGARUH LATIHAN SHOULDER FLEXSION TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA EXTRAKULIKULER BOLA VOLI SISWI SMK TARUNA MANDIRI PEKANBARU - ', Slamet; Wijayanti, Ni Putu Nita; afda’u, Muhammad Faisal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: the purpose of research find out if there is any influence Shoulder Flexion practice about the muscle strength of the arms and shoulders on extracurricular volleyball student of SMK Taruna Mandiri of Pekanbaru so when serving bottom get maximum results. This form of research is treatment (Experimental) research’s, population in this study is students of SMK Taruna Yayasan Mandiri Pekanbaru, the sample in this study is the entire population of 8 people. Instruments performed to know the muscle strength of the arms and shoulders, in this study is the expanding dynamometer test. After that the data is processed with statistics, to test the normality by liliefors test at a significant level α 0.05. The hypothesis proposed is there is an effect of Shoulder Flexion practice against the muscles of the arms and shoulders. Analysis of t produces thitung equal to 7,61 and ttable equal to 1,895, be significant Thitung>Ttabel. Pursuant analysis according to statistics, there is an average free-test equal to 19,1875, and the post-test average of 24.1375, the mean data is normal. Therefore, there is an effect of Shoulder Flexion practice muscle strength of arms and shoulders on extracurricular volleyball students SMK Taruna Mandiri of Pekanbaru.Keywords: Arm muscle strength and shoulders, Shoulder flexsion